Double eagle - Collard, Sneed B. (Atlanta, Ga. : Peachtree, 2009)
Michael and Kyle's discovery of a rare Confederate coin near an old Civil War fort in 1973 turns into a race against time as the boys try to find more coins before a hurricane hits Alabama's Gulf coast.
Includes bibliographical references (p. 242).
5.2
5-8
Keywords: Coins -- Collectors and collecting -- Juvenile fiction; Hurricanes -- Juvenile fiction; Treasure troves -- Juvenile fiction; Buried treasure -- Fiction; Coins -- Collectors and collecting -- Fiction; Hurricanes -- Fiction; Buried treasure -- Fiction; Coins -- Collectors and collecting -- Fiction; Hurricanes -- Fiction; Alabama -- History -- 1951- -- Juvenile fiction; Alabama -- History -- Fiction; Alabama -- History -- Fiction